Coastal fish diversity of the Socotra Archipelago, Yemen - Zajonz, Uwe; Lavergne, Edouard; Bogorodsky, Sergey V.; Saeed, Fouad Naseeb; Aideed, Moteah Sheikh; Krupp, Friedhelm (Zootaxa, 2019)
The Socotra Archipelago, located in the eastern Gulf of Aden, has a unique marine environment which combines tropical and ‘pseudo-temperate’ elements. Studies on the fish biogeography of the archipelago, partially framed in regional studies, have substantially outpaced critical elementary research on the archipelago’s fish diversity. The present study seeks to close this gap and identifies the Socotra Archipelago as a major hotspot of coastal fish diversity in the Indian Ocean. The archipelago supports unique coastal fish assemblages which are predominantly composed of coral-associated (“reef”) species, in spite of the limited biogenic reef frameworks. A Preliminary Checklist comprises 682 species with confirmed records and a “Working List” includes an additional 51 records, totalling 733 faunal records in 108 families. The family Labridae is the most speciose, followed by Gobiidae, Pomacentridae, Serranidae and Chaetodontidae. The species richness of the archipelago is the highest when compared to adjacent Arabian ecoregions. The richness of the Acanthuridae, Chaetodontidae, Labridae, Pomacentridae and Pseudochromidae stand out as particularily high, and the richness of several families is as high as or higher than in the entire Red Sea. The total archipelagic richness is extrapolated at up to 875 species based on incidence-based richness models and expert opinion. Inshore fish inventories, covering 497 species, found between 14 and 132 species per site (x̄ = 66). Site diversity decreased across the archipelago from west to east and from north to south. Total fish diversity was highest around Socotra Island, followed by Abd al-Kuri & Kal Farun and Darsa & Samha. Occurrence frequencies were very unevenly distributed and dominated by Pomacentrus caeruleus and Thalassoma lunare, whilst many species were infrequent. The fish assemblages are dominated by species from the Indo-West Pacific and the north-western Indian Ocean. The assemblages are rich in rare species and hybrids, and include a low number of endemics (4–5), and a high number of species with far-reaching and Western Indian Ocean ranges.